2019
DOI: 10.1177/1359104519833737
|View full text |Cite
|
Sign up to set email alerts
|

Relating mindfulness and executive function in children

Abstract: Despite the important role of cognitions in mindful awareness, research on the cognitive processes underlying mindfulness in young populations is scarce. This study explores the association between the core executive functions (i.e. inhibition, working memory, and shifting) and mindfulness within the same model in a sample of children. Seventy-two parent–child dyads participated in the study. Difficulties with executive functioning and child mindfulness level were assessed. Inhibition, working memory, and shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
(78 reference statements)
3
19
0
1
Order By: Relevance
“…Although the study was limited in that it used survey data, it reported a negative correlation between mindfulness and difficulties with inhibition, working memory, and shifting, confirming that children who were more mindful were less likely to experience such difficulties. Our results strengthened those correlational findings obtained indirectly by using child and parent ratings [ 42 ]. Indeed, by administering mindfulness training and analyzing its effects on neuropsychological measures that involve executive functions, we directly verified the relationship between mindfulness and executive functions.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Although the study was limited in that it used survey data, it reported a negative correlation between mindfulness and difficulties with inhibition, working memory, and shifting, confirming that children who were more mindful were less likely to experience such difficulties. Our results strengthened those correlational findings obtained indirectly by using child and parent ratings [ 42 ]. Indeed, by administering mindfulness training and analyzing its effects on neuropsychological measures that involve executive functions, we directly verified the relationship between mindfulness and executive functions.…”
Section: Resultssupporting
confidence: 91%
“…Our tasks involved higher-order cognitive abilities, such as working memory, inhibitory control, switching, and sustained performance. However, there are few data on the association between mindfulness and executive functions [ 79 , 80 , 81 ] in typically developing children [ 42 ] and in children with neurodevelopmental disorders, having been studied primarily in adult populations and adolescents [ 82 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, even with an increasing number of studies targeting neurocognitive mechanisms in children and adults (Flook et al, 2010;Moore & Malinowski, 2009;Schonert-Reichl et al, 2015), there are currently no studies that have measured the change in EFs after a school-based intervention, combining active control groups, comprehensive neurocognitive measures, and follow-up (Bradshaw et al, 2012;Chiesa & Serretti, 2010;Tan, 2016). Moreover, the number of participants in the majority of studies that explore the core EFs and mindfulness is generally small (N < 100) (Schonert-Reichl et al, 2015;Wimmer, Bellingrath, & Stockhausen, 2016) In correlational studies, researchers have found a significant correlation between state mindfulness and working memory capacity among 12-16-year-old (Natesh, Rajesh, & Nagendra, 2014) and inhibition, working memory, and attention shifting among 7-13-old students (Geronimi, Arellano, & Woodruff-Borden, 2020). So far, only a few intervention studies among children and adolescents focusing on specific EFs and mindfulness-related benefits have been carried out, showing mixed results.…”
Section: Introductionmentioning
confidence: 99%